Natural incidence of pathogenic fungi on stink bug pests in Argentinian rice paddies. Issue 7 (27th March 2022) - Fuentes, Daniela; Toledo, Andrea; Pedrini, Nicolás; Sosa, Alejandro; Santana, Marianela; Gervazoni, Paula; Dellapé, Gimena; Franceschini, Celeste
Abstract: Entomopathogenic fungi (EF) are important biocontrol agents due to their wide host range, easy application, and compatibility with phytosanitary products. Stink bugs (Hemiptera: Pentatomidae) are the most important rice pests in Argentina. Although there is information on the pathogenicity of EF against stink bug pests in rice fields, the natural incidence of EF, and especially their association with stink bug species and plant characteristics, is largely unexplored. The aims of this study were: (1) to monitor the natural incidence of EF on Pentatomidae pests in Argentinian rice paddies; (2) to assess the relationship between the incidence of EF, stink bug feeding guild, and rice cultivar; and (3) to perform a phylogenetic analysis of the EF recorded. Sampling was conducted in target rice fields throughout the rice‐growing season (2017–2018), during which adult individuals of Tibraca limbativentris Stål and Oebalus spp. were manually collected and visually examined for evidence of mycelial development. Of the 780 individuals examined, 182 infected individuals were recorded, from which 12 strains of EF were isolated and identified based on molecular characterization: three strains of Beauveria bassiana sensu lato (Bals.‐Criv.) Vuill., five of Metarhizium anisopliae s.l. (Metschn.) Sorokin, and four of Purpureocillium lilacinum (Thom) Luangsa‐ard et al. (Hypocreales). The occurrence of the three EF species was significantly higher in stem‐feeding T. limbativentris than in seed‐feeding Oebalus spp., thus, differed between feeding guilds. For T. limbativentris, the occurrence of EF was higher when feeding on a short than on a tall rice variety, thus, differed between plant varieties. The results illustrate the potential of using native strains of EF in integrated management of stink bugs in rice. Abstract : Entomopathogenic fungi (EF) are important biocontrol agents. Stink bugs (Hemiptera: Pentatomidae) are major rice pests in South America, but the natural incidence of EF in relation to insect species and plant characteristics is largely unexplored. We collected stink bugs of two genera from two rice varieties in Argentina and assessed EF presence. The occurrence of EF differed among pest feeding guilds and rice varieties. These results show the potential of using native EF strains in integrated management of rice pests.